Pengaruh Entrepreneurial Orientation terhadap Financial Performance melalui Competitive Advantage dan Job Satisfaction sebagai Variabel Intervening pada Perusahaan Publik Sektor Manufaktur di Surabaya dan Sidoarjo - Marcellina Hariyanto; Devie Devie Devie (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of entrepreneurial orientation to competitive advantage, entrepreneurial orientation to job satisfaction, competitive advantage to financial performance, job satisfaction to financial performance, on go public manufacturing firms in Surabaya and Sidoarjo. This study used quantitative approach, and the data obtained through the distribution of questionnaire and used ratio financial statement analysis to go public manufacturing firms in Surabaya and Sidoarjo processed by using SmartPLS software. This study showed that there was a positive and significant relationship of entrepreneurial orientation to competitive advantage, entrepreneurial orientation to job satisfaction, entrepreneurial orientation to financial performance, competitive advantage to financial performance, job satisfaction to financial performance, and job satisfaction to competitive advantage on go public manufacturing firms in Surabaya and Sidoarjo. competitive advantage and job satisfaction became the intervening variables to entrepreneurial orientation and financial performance.